The capacity of crab megalopae to autotomize body appendages and the consequences upon their feeding ability - the price to pay to live another day - Calado, R.
During the mass settlement events of brachyuran crabs, there is a significant chance of density-dependent injury in the megalopae (last larval stage) because cannibalism can occur by larger conspecifics. Laboratory observations revealed that the appendages that are more prone to injury are eyestalks, as well as first (P1) and fifth (P5) pereiopods. The ability of Carcinus maenas megalopae to autotomize these structures and the effect of such injuries in their feeding ability and metamorphosis were investigated. All tested specimens were able to autotomize one or both of their P1 and P5, but not their eyestalks. Megalopae missing a single P1, as well as one or both P5, were able to capture and ingest prey, as well as intact specimens. Megalopae with either P1 and P5 appendages or at least one damaged eyestalk failed to ingest sufficient food to reach the nutritional threshold required to successfully metamorphose.